2020
DOI: 10.1016/j.molmet.2020.101094
|View full text |Cite
|
Sign up to set email alerts
|

Ozone-induced fetal growth restriction in rats is associated with sexually dimorphic placental and fetal metabolic adaptation

Abstract: Objective The importance of the placenta in mediating the pre- and post-natal consequences of fetal growth restriction has been increasingly recognized. However, the influence of placental sexual dimorphism on driving these outcomes has received little attention. The purpose of this study was to characterize how sex contributes to the relationship between placental metabolism and fetal programming utilizing a novel rodent model of growth restriction. Methods Fetal growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…Prenatal exposure to BPA in CD-1 mice induced increased weight gain, reduced glucose tolerance, increased abdominal fat mass, and increased insulin levels in male offspring [ 71 ]. Recent work evaluating the effect of ozone exposure during gestation on offspring in rats found that programming of metabolic pathways in the fetal liver is impaired in males, but not females [ 72 ]. Increased sensitivity in males compared to females has also been well documented in toxicology studies [ 73 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal exposure to BPA in CD-1 mice induced increased weight gain, reduced glucose tolerance, increased abdominal fat mass, and increased insulin levels in male offspring [ 71 ]. Recent work evaluating the effect of ozone exposure during gestation on offspring in rats found that programming of metabolic pathways in the fetal liver is impaired in males, but not females [ 72 ]. Increased sensitivity in males compared to females has also been well documented in toxicology studies [ 73 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of non-pregnant individuals on the inhalation in urban settings of ambient particles and ozone for 2 h led to arterial vasoconstriction in healthy adults [ 106 ]. Ozone exposure during implantation appears to induce fetal growth restriction due to decreased uterine blood flow and is used to generate models of fetal growth restriction in pregnant Long-Evans rats [ 107 ]. Acute systemic inflammation and oxidative stress following PM exposure, as described above, are likely responsible for triggering endothelial dysfunction leading to vasoconstriction [ 56 , 82 , 108 ].…”
Section: Introductionmentioning
confidence: 99%
“…When the intrauterine environment is disturbed in rodents and humans, placentas with male fetuses consume more energy to accelerate its own growth as well as the fetus’, accelerating epigenetic aging at the expense of adaptability and plasticity ( Tekola-Ayele et al, 2019 ; Yu et al, 2021 ). In contrast, placentas with female fetuses respond to disturbances with protective mechanisms such as slowing down growth and metabolism to ensure fetal survival ( Miller et al, 2020 ; Phuthong et al, 2020 ; Saoi et al, 2020 ; Weinheimer et al, 2020 ). These different growth strategies in response to disturbances may place male fetuses at a greater risk when exposed to POPs or other disturbing pollutants.…”
Section: Introductionmentioning
confidence: 99%